INVESTASI EMAS PADA MASA PANDEMI COVID 19 (KAJIAN KRITIS SECARA ISLAM) - Yana Dwi Christianti; RB. Iwan Noor Suhasto; Rosyida Nurul Anwar (ITB AAS INDONESIA Surakarta, 2022)
This study aims to see how the impact of the Covid 19 pandemic on investment activities, especially gold investment. The research method used is qualitative research using library research methods and documentation, the data used in this research is primary and secondary data. The subject of this study is the people who invested in gold during the pandemic. The results of this study are expected to provide an overview and input related to the development of gold investment in Indonesian society, which mostly adheres to Islam.